An evaluation of the participation of selected project participants in the Kalahi-CIDSS project in Barangay Calzada, Jovellar, Albay - Mijares, Joel S. (2006)
Participation is both a means and an end and can be described as a continuum ranging from the contribution of inputs, decision-making, partnership, and empowerment. It could take place indifferent stages of the project cycle, at different levels of society, and in different forms. This study was conducted to gauge community empowerment by evaluating the type or mode and level of participation of selected participants in the Kalahi-CIDSS Project in Barangay Calzada, Jovellar, Albay.The evaluation took into consideration their roles and functions in the 16-step sub-project cycle and evaluated these against the KC typology of participation and Hollnsteiner"s framework on participation. Kapit-Bisig Laban sa Kahirapan-Comprehensive and Integrated Delivery of Social Services :Kapangayarihan at Kaunlaran sa Barangay (Kalahi-CIDSS : KKB ) Projectis a community -driven development project and its main objective is to empower communities through their enhanced participation in community projects that reduce poverty. The results of the study showed that the level of participation of selected projects participants dwelled on passive participation with minimal decision-making. All groups, with the exception of the barangay representation team (BRT), were in the passive mode of participation and empowerment at the minimal levele. The participation of the barangay representation team (BRT) in project activities in the municipal inter-barangay forum gave the team substantial involvement in priotizing projects, in the formulation of plans, and in deciding on the manner of implementing them. The attendance and the roles performed by the respondents in the KC planning cycle were described as in compliance with the requirements of the Project. Most of the activities attended were on information dissemination, data gathering and analysis, and plan implementation--activities described as non-decision-making. The study recommends that poverty group-focused planning approach should be adopted, to encourage participation among the local residents. Provision of livelihood support fund to entrepreneural poor is also recommended to provide opportunities for participation and at the same time enhance capabilities in project and financial management. The study also recommends that a matrix that would describe the mode of participation appropriate or relevant at each stage of the planning cycle should be developed to establish the relationship between participation and the different stages of the project cycle. The matrix would help determine exactly what process of participation will be involved during the course of the project implementation. Activities and approaches could be developed and designed to fit with the goals and objectives of the project and the purpose of the participation of the stakeholders.Recommendations for future studies inculde the following: (1) an evaluation of the aprticipation of pre-selected or pre-identified local agencies in other development projects to know the level of involvement and roles of these agencies to gauge the impact of the projects; (2) a study on how participation of specific stakeholders affects the type and quality plans; and (3) a study to determine the types of plans produced when project mode of planning is done and what types of plans are produced when institutional mode of planning is adopted.